Development and validation of a species-specific environmental DNA (eDNA) primer for endangered Asian arowana, Scleropages formosus (Teleostei: Osteoglossidae) for law enforcement and wild population monitoring - Nurul Affiqah Edora Mohd-Azhar; Haslawati Baharuddin; Mohamad-Sufiyan Salmi; Noor Faizah Ismail; Amatul-Samahah Md. Ali; Syazwan Saidin; Adibah Abu-Bakar (MethodsX)
The Asian Arowana, Scleropages formosus (Müller and Schlegel, 1844) is a large majestic freshwater teleost, crowned as the king of aquariums with its bright charismatic appearance and magnificent swimming performance. The most expensive Asian arowana is the Golden Blue-based Malayan Arowana which is endemic to the Bukit Merah Lake and Kerian River Basin, Perak, Malaysia. S. formosus has been listed as endangered by the IUCN (International Union for Conservation of Nature), regulated under Appendix 1 of the Convention of International Trade on Endangered Species (CITES) for commercial trade. Environmental DNA (eDNA) analysis has become widely accepted in biodiversity monitoring for the detection of rare and endangered species without harming any ecosystem or threatened species. Hence, the application of eDNA as wild population monitoring of S. formosus is possible for conservation and CITES enforcement program. • The species-specific primer of S. formosus was designed based on selected sequences obtained from GenBank • This report presents the potential application of eDNA in the management of the Malaysian 686 CITES Act for conservation monitoring of the Asian Arowana • The detection and wild population monitoring is possible through the eDNA method as complementary tools